2020
DOI: 10.21608/sinjas.2020.36229.1003
|View full text |Cite
|
Sign up to set email alerts
|

Beef Burger Quality Characteristics and Shelf Life Improvement by Marjoram Addition

Abstract: Marjoram was applied to beef burger to improve its physical and chemical properties and to extend its shelf life. Marjoram was added to beef burger in two forms; ethanolic extract at 0.1, 0.2 and 0.3 g/100g and as dry powder at 0.2, 0.4 and 0.6 g/100g and was stored at freezer (-18℃) for three months. Chemical properties including moisture, protein, fat contents and pH values, physical properties (water holding capacity), cooking characteristics (shrinkage, cooking loss and cooking yield), shelf life limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings agree with those of Ragab et al [41], who concluded that the protective impact of marjoram against microbes that accelerate the breakdown of protein to volatile nitrogen during preservation could be attributed to the reduced TVN levels. In addition, Kowalczyk et al [42] discovered that the inclusion of chokeberry leaf extract, relative to the controls, increases the shelf-life storage time, according to instrumental.…”
Section: Effect Of Storage Period On Tba and Tvn Values Of Burgersupporting
confidence: 93%
“…These findings agree with those of Ragab et al [41], who concluded that the protective impact of marjoram against microbes that accelerate the breakdown of protein to volatile nitrogen during preservation could be attributed to the reduced TVN levels. In addition, Kowalczyk et al [42] discovered that the inclusion of chokeberry leaf extract, relative to the controls, increases the shelf-life storage time, according to instrumental.…”
Section: Effect Of Storage Period On Tba and Tvn Values Of Burgersupporting
confidence: 93%
“…It is noticeable that the microbial load decreases with the increase in the addition, as the percentage of addition 3.5% recorded the noticeable increase decrease in the microbial count compared to the control; it could be mainly attributed to the antimicrobial and antioxidant properties of phenols and flavonoids. It worth to note that the microbial quality standards tested for beef burger were within the permissible limits of [47]. By comparing Table 6 and Table 7 of galangal powder and galangal extract, the table of galangal powder recorded a lower number of microbial growths during storage periods than galangal extract percentage of Even in the high percentage of adding galangal extract 15%.…”
Section: Changes In Microbiological Load Of Beef Burger Incorporated ...mentioning
confidence: 71%
“…After homogenizing samples for a minute by a stomacher, we incubated them at 35 • C/24 h. Following this pre-enrichment, we added 1 mL of the mixture to 9 mL of peptone broth and incubated it at 35 • C/24 h. To count pathogenic bacteria, we surface-plated the samples with the proper dilutions and duplicated them on Tryptic Soy Blood Agar (TSBA) medium plates. We conducted three individual replicates of each experiment to ensure accuracy as reported by Ragab et al and Hamad et al [45,46].…”
Section: Shelf-life For Padina Pavonica Extract As Antibacterial On B...mentioning
confidence: 99%